Effects of the Changes in the Neutron Number of Isotonic Nuclei on the Tow-Component Partial Level Density Formula Corrected for Pairing in Pre-Equilibrium Reactions - Mohammad, J. F.; Salloum, A. D.; Al-Jabbar, H. A. (Iraqi Journal of Science, 2022)
Ericson’s formula describes the partial level density (PLD) of pre-equilibrium reactions and corrections. PLD with pairing correction can be calculated using four methods, namely, pairing, improved pairing, exact Pauli and back shift energy corrections. The variations in the PLD values of each of the four formulas of strontium (88Sr), Yttrium (89Y) and Zirconium (90Zr) isotones have been examined. Results shows that the PLD values that use pairing and improved pairing corrections do not vary for different isotones. However, a small change in PLD values is observed when exact Pauli correction and back shift energy were utilised. The change in the PLD values using back shift energy correction is bigger than the values obtained by using exact Pauli correction. Therefore, the use of back shift formula is recommended because it results in noticeable changes with any small increase in mass number.